On the osteology of a distinctive specie of the genus Leptodactylus: Leptodactylus laticeps (Boulenger, 1917) (Anura, Leptodactylidae) - Ponssa, María L. (Zootaxa, 2006)
The osteology of Leptodactylus laticeps is described. This species is the most distinctive member of the pentadactylus species group, and possibly of the genus Leptodactylus, based on external morphology, skin secretions and some aspects of its life history. This paper notes some characters that differ from or were previously overlooked in, description of the Leptodactylus. These are: 1) arrangement cotylar type II, 2) sacral diapophyses expanded, 3) nasals contiguos or in contact with frontoprietals, and 4) an anterior ramus parasphenoid which can or cannot reach the palatines. Some characters could be useful for species diagnoses and/or phylogenetic studies, such as elongation of the pars facialis of maxilla, maxillary teeth found almost reaching quadratojugal or extending beyond quadratojugal, nasals with posterolateral projections very prominent, nasals almost or in contact with each other; high number of vomerine teeth, tip of palatines not acute, and an alary process of premaxilla which is oriented slightly postero-dorsally.